Da’wah Cultural Through The Tolak Bala Ritual In Kuin Besar Village - Nasruddin Nasrullah; Nur Falikhah; Zulfa Jamalie (Alhadharah: Jurnal Ilmu Dakwah, 2023)
The Tolak Bala ritual in Kuin Besar Village pray for safety and protection from God so that they are safe, protected from all kinds of disaster. This ritual will be seen from an anthropological religion approach where the object is the diversity of society, which is empirical, appears to be valid and not based on right or wrong judgments. So how does the Tolak Bala ritual become part of the urang banjar culture and the values contained therein are analyzed in depth. This research is a field research with data collection methods, namely observation and interviews. The results of the study show that the Tolak Bala ritual is a culture which is embodied in cultural systems, social systems and artifacts. This ritual also represents solidarity, the situation is okay, a harmonious condition among its citizens. There are da'wah values in this ritual, namely strengthening friendship, giving thanks, covering the genitals, inviting the community to give alms, working together and holding deliberations. With these positive values, the tradition of Tolak Bala reinforcements can be used as a medium for preaching or commonly called da’wah cultural.